Differential effects of prostaglandin derived from ω-6 and ω-3 polyunsaturated fatty acids on COX-2 expression and IL-6 secretion - Bagga, Dilprit (The National Academy of Sciences, 2003)
Omega-6 (ω-6) polyunsaturated fatty acids (PUFA), abundant in the Western diet, are precursors for a number of key mediators of inflammation including the 2-series of prostaglandins (PG). PGE(2), a cyclooxygenase (COX) metabolite of arachidonic acid, a ω-6 PUFA, is a potent mediator of inflammation and cell proliferation. Dietary supplements rich in ω-3 PUFA reduce the concentrations of 2-series PG and increase the synthesis of 3-series PG (e.g., PGE(3)), which are believed to be less inflammatory. However, studies on cellular consequences of increases in 3-series PG in comparison to 2-series PG have not been reported. In this study, we compared the effects of PGE(2) and PGE(3) on (i) cell proliferation in NIH 3T3 fibroblasts, (ii) expression and transcriptional regulation of the COX-2 gene in NIH 3T3 fibroblasts, and (iii) the production of an inflammatory cytokine, IL-6, in RAW 264.7 macrophages. PGE(3), unlike PGE(2), is not mitogenic to NIH 3T3 fibroblasts. PGE(2) and PGE(3) both induce COX-2 mRNA via similar signaling mechanisms; however, compared with PGE(2), PGE(3) is significantly less efficient in inducing COX-2 gene expression. Furthermore, although both PGE(2) and PGE(3) induce IL-6 synthesis in RAW 264.7 macrophages, PGE(3) is substantially less efficient compared with PGE(2). We further show that increasing the ω-3 content of membrane phospholipid results in a decrease in mitogen-induced PGE(2) synthesis. Taken together, our data suggest that successful replacement of ω-6 PUFA with ω-3 PUFA in cell membranes can result in a decreased cellular response to mitogenic and inflammatory stimuli.